Educational Interaction of Prophet Musa and Khidir in The Perspective of Al-Quran - Afrizal Syahputra (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
This research examines the meeting of the Prophet Musa and Khidir which is mentioned in the Al Qur'an in al-Kahfi. They met at a place called